TRAILER: Two degrees up - International Center for Tropical Agriculture (2010)
Turn on your speakers, then double-click to watch on the big screen. Early December 2010 will bring exciting news from CIAT and the CGIAR, as well as 3 high-quality digital stories giving a unique insight into what a two-degree rise in average temperatures could mean for farmers in Colombia, Ghana and Kenya. This movie trailer for the Two Degrees Up project gives you a sneak preview of what's coming soon. Pics, music and trailer by Neil Palmer.